Pragmatic enterprise architecture : strategies to transform information systems in the era of big data - Luisi, James V. (Morgan Kaufmann, 2014)
Pragmatic Enterprise Architecture is a practical hands-on instruction manual for enterprise architects. This book prepares you to better engage IT, management, and business users by equipping you with the tools and knowledge you need to address the most common enterprise architecture challenges. You will come away with a pragmatic understanding of and approach to enterprise architecture and actionable ideas to transform your enterprise. Experienced enterprise architect James V. Luisi generously shares life cycle architectures, transaction path analysis frameworks, and more so you can.